Evidence for the spontaneous formation of N-heterocyclic carbenes in imidazolium based ionic liquids. Issue 81 (11th September 2017) - Daud, N. M. A. N.; Bakis, E.; Hallett, J. P.; Weber, C. C.; Welton, T.
Abstract : Evidence is presented for the spontaneous formation of N-heterocyclic carbenes in ionic liquids based on 1, 3-dialkyl substituted imidazolium cations. Abstract : We present a study of the reactions of aldehydes in ionic liquids which gives evidence for the spontaneous formation of N-heterocyclic carbenes in ionic liquids based on 1, 3-dialkyl substituted imidazolium cations from the lack of a deuterium isotope effect on the reaction of these ionic liquids with aldehydes.